Lauten in regionalen kulturbildern des orients : barbat, gambus, ud und pipa. - Jaehnichen, Gisa (Are Musik, 2012)
Lutes are well respected as indicators of a certain development regarding their material and technological as well as their intellectual level in various histories of oriental cultures. They are considered especially interesting concerning questions about acculturations, transculturations and re-definitions of cultural affiliation, which are represented in the stock of musical instruments of different regions. Though the four names of the lutes barbat, gambus, ud and pipa are already very abstract terms in their actual developing context of cultural life, they mark an important status of musical coexistence of lutes and imply tangible and intangible relations between them. However, I want to apply these terms for being used in the affiliated cultures with a quite clear understanding of their actual differences that are connected to their history and to their social condition.